O uso das plantas medicinais pelas mulheres das comunidades rurais de Upanema, RN - Rocha, Eva Siqueira da (Universidade Federal Rural do Semi-Árido, 2019)
This work presents considerations about the cultivation and the use of medicinal plants by women from rural communities in the municipality of Upanema, RN. The objective of this research was to analyze the cultural historical process of the different types of use of medicinal plants by these women. The choice of theme was made through my coexistence with the women of those communities when I attended the meetings of the Maria Celeste Association in the Cacimba do Meio Community and visiting their backyards. The methodological process was done through semi-structured interviews of a qualitative nature, using the dynamics of the snowball, where the first woman interviewed indicated me another woman successively, in order to approach them. Interviews were conducted with four women. Therefore, was possible to verify that women prefer to treat their illnesses with the medicinal plants grown in their backyard, such as rue, acerola, holy grass, yellow cashew, citrus herb, partel's mint, peppermint, lemon, mallow, thick mauve, mastruz, meracillin and pomegranate. But they also use medicinal plants from the wild forest such as chanana, purge potato, fedegoso, jatoba, pinto chick, white quixaba. Women prepares bottles, lickers and tea with these medicinal plants. This practice was learned from their mother, grandparents, and aunts, and pass this knowledge on to family members and acquaintances. However, they resort to the municipal health system, when they can not treat their health problems with the mentioned medicinal plants. From this work it was possible to verify that the use and cultivation of medicinal plants by women in rural communities are related to cultural customs, even though they have access to the municipal health system, many treat their illnesses with medicinal plants, but when they do not, they seek medical help at home. Thus, revealing the union of home treatment with traditional medicine, the resistance of women and the coping with the health problems that usually arise. The common interest that exists among these women, who are willing to help others in the fight against disease, is very striking and touching, as they are willing to help, without any financial interest, everything is based on respect for others. This knowledge is passed on to their descendants and neighbors for the well-being of health among these rural communities.
Monografia
Keywords: Semiárido; Caatinga; Mulheres; Cultura; Semiarid; Caatinga; Women; Culture; CIENCIAS HUMANAS::EDUCACAO::TOPICOS ESPECIFICOS DE EDUCACAO::EDUCACAO RURAL